A new species, new synonymy, and taxonomic notes in the Anastrepha schausi group (Diptera: Tephritidae) - Norrbom, Allen L.; Korytkowski, Cheslavo A. (Zootaxa, 2007)
Anastrepha fuscicauda Norrbom & Korytkowski, new species, is described from Panama. Anastrepha bellicauda Norrbom is considered a new junior synonym of A. lutea Stone, a sexually dimorphic species which is redescribed.Se describe una nueva especie de Anastrepha desde Panamá, Anastrepha fuscicauda Norrbom & Korytkowski. Anastrepha bellicauda Norrbom es un sinonimo nuevo de A. lutea Stone, una especie con sexos dimorficos.